Competition and risk-taking in investment banking - Degl'Innocenti, Marta; Fiordelisi, Franco; Girardone, Claudia; Radić, Nemanja (Wiley, 2019)
How does competition affect the investment banking business and the risks individual institutions are exposed to? Using a large sample of investment banks operating in seven developed economies over 1997-2014, we apply a panel VAR model to examine the relationships between competition and risk without assuming any a priori restrictions. Our main finding is that investment banks’ higher risk exposure, measured as a long-term capital-at-risk and return volatility, was facilitated by greater competitive pressures especially for full service investment banks but also for boutique investment banks. Overall, we find some evidence that more competition leads to more fragility before and during the recent financial crisis.
Keywords: competition; investment banking; panel var; Risk; D4; G3; G24